Relationship between organochlorine contaminants and mixed function oxidase activity in skin biopsy specimens of Mediterranean fin whales (Balaenoptera physalus) - MARSILI, L.; FOSSI, M. C.; NOTARBARTOLO DI SCIARA, G.; ZANARDELLI, M.; NANI, B.; PANIGADA, S.; FOCARDI, S. (Chemosphere, 1998)
The relationship between organochlorine contaminants (PCBs and DDTs) and mixed function oxidase, benzo(a)pyrene monooxigenase activity (BPMO), was investigated in skin biopsy specimens from fin whales (Balaenoptera physalus) of the Mediterranean Sea. Skin biopsy material sampled by a non invasive technique, is suitable for a wide range of chemical and biomarker analysis. In this study PCBs and DDTs were evaluated in subcutaneous blubber and MFO activity in epidermis. An interesting correlation was found in male specimens between the two variables.